(untitled) (Eurasian Scientific Herald, 2024)
In this article, the application of pedagogical technologies in the educational process is considered one of the most urgent tasks today and is covered in a very broad sense. Today, teaching based on pedagogical technologies in the primary education process is considered the demand of the era